32.9k views
2 votes
Solve for x.
2 (x − 3) = 8 (x − 6)
-
Enter your answer in the box.

1 Answer

4 votes


2 (x - 3) = 8 (x - 6)

Distribute:


(2)(x)+(2)(-3)=(8)(x)+(8)(-6)


2x-6=8x-48

Subtract 8x from both sides:


2x-6-8x=8x-48-8x


-6x-6=-48

Add 6 to both sides:


-6x-6+6=-48+6


-6x=-42

Divide both sides by -6:


(-6x)/(-6) =(-42)/(-6)


\fbox{x = 7}

User Muhammad Chhota
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.